ANALISIS FINANSIAL USAHA ABON IKAN TUNA (Thunnus sp) PRODUKSI UMKM KOTA PAREPARE - Arman, Arman; Ruslang, Ruslang (Universitas Negeri Makassar, 2017)
Efforts to enhance the value and optimize the utilization of the production of marine catches is to develop value-added products, both traditional and modern processed. One of the many Tuna fish processing done by community group, both home industry and UMKM is abon industry. The abon industry in Parepare city by UMKM